(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2025)
About the volume by Arthur McCalla, Religion and the Post-Revolutionary Mind: Idéologues, Catholic Traditionalists, and Liberals in France, Montreal, McGill-Queen’s University Press, 2023, 464 p.